Students’ attitude towards Undergraduate Foundation Mathematics Remediation in a HE institution in a Gulf Country (INTERNATIONAL JOURNAL OF RESEARCH IN EDUCATION METHODOLOGY, 2019)
This study outline causes why Foundation Mathematics students are reluctant to access support and remedial structures that are put in place to enable them to achieve their academic goals.  The study was conducted using a survey method which included administering a structured questionnaire and one-to-one focused group discussions with students. The study aims to discuss the common tendency of students towards mathematics remediation programmes. This study centred on students’ perceptions regarding the teaching & Learning of Mathematics, specifically, however, the educational surroundings impacts their perceptions as students of Mathematics in terms of confidence, anxiety, enjoyment, motivation, and therefore the connection of Mathematics in personal and skilled Experiences. Data obtained from this study indicated that factors contributing to poor performance include lack of motivation, poor attitude of students towards Mathematics courses and retrogressive practices. It is envisaged that rising on these factors and sensitization of students to discard practices that proscribe learner’s effective participation in finding out the topic may improve their performance in mathematics. It is likely that improved mathematics performance will give learners opportunities to pursue mathematics-related HE degree programmes at higher institutions of learning.